CircBIRC6 facilitates the malignant progression via miR-488/GRIN2D-mediated CAV1-autophagy signal axis in gastric cancer - Zhiyuan Tang; Jieying Li; Bing Lu; Xiaojing Zhang; Lei Yang; Yue Qi; Sutian Jiang; Qianqian Wu; Yingjing Wang; Tong Cheng; Manyu Xu; Pingping Sun; et al. (Elsevier, 2024)
Circular RNAs (circRNAs) represent a novel class of non-coding RNAs that play significant roles in tumorigenesis and tumor progression. High-throughput sequencing of gastric cancer (GC) tissues has identified circRNA BIRC6 (circBIRC6) as a potential circRNA derived from the BIRC6 gene, exhibiting significant upregulation in GC tissues. The expression of circBIRC6 is notably elevated in GC patients. Functionally, it acts as a molecular sponge for miR-488, consequently upregulating GRIN2D expression and promoting GC proliferation, migration, and invasion. Moreover, overexpression of circBIRC6 leads to increased GRIN2D expression, which in turn enhances caveolin-1 (CAV1) expression, resulting in autophagy deficiency due to miR-488 sequestration. This cascade of events significantly influences tumorigenesis in vivo. Our findings collectively illustrate that the CircBIRC6-miR-488-GRIN2D axis fosters CAV1 expression in GC cells, thereby reducing autophagy levels. Both circBIRC6 and GRIN2D emerge as potential targets for treatment and independent prognostic factors for GC patients.